Integrated pest management in Peru - Palacios Lazo, María; Lizárraga Travaglini, Alfonso; Velásquez Ochoa, Edwin Ricardo; Carranza Hernández, Enrique; Segovia, Isaías (CABI Publishing, 2022)
12 páginas